Avaliação de Bacias de Detenção na gestão de águas pluviais em Araraquara, SP - Peroni, Carolina Sulzbach Lima (2018)
The quest for the mitigation of the impacts of urbanization on stormwater runoff and infiltration gave rise, in the 1970s, to the compensatory techniques on urban drainage. These techniques, which were widespread in North America and Europe, were strengthened in the 1990s, with emphasis on detention basins, which are unique for the control of peak flows with Great return times. In the past decade, this trend has intensified in medium-sized cities, such as the municipality of Araraquara, São Paulo, which requires the construction of these basins for new subdivisions. In this context, the present research has the objective of evaluating 3 Detention Basin Systems (DBS) and 20 Detention Basins (DB) constructed in the urban environment of the Municipality of Araraquara, SP, regarding urban insertion, maintenance and integration of these units with their environments. In order to reach this goal, the DBS and DB inserted in the municipality were identified, characterized and mapped using satellite images, on-site visits and the QGIS software version 2.14.13-Essen, respectively. Variables were defined for the evaluation of the units that include aspects of direct observation of the units with and without the precipitation event; aspects of design, construction and operation of the units; and aspects of population perception regarding units. It is necessary to use questionnaires to obtain data, particulary those referring to engineering projects and maintenance practices, as well as the perception of the population neighboring the units. This methodology is expected to identify similarities and discrepancies of insertion and the maintenance of the studied units. In a preliminary way, SBD and SB were found to be located in the Ribeirão das Cruzes sub-basin and distributed upstream of the Cruzes Dam (surface catchment point), even though this is a region susceptible to erosive processes and geotechnical risk. It was also observed a tendency to implant these units isolated from their surroundings, without their integration with urban space, and exclusively focused on the hydrological function. In terms of maintenance, the basins prove to be inadequate, largely due to the excess vegetation, as well as the presence of sediments inside them. The depredation of insulation structures (fence and gate) as well as the inadequate disposal of solid waste, especially those from demolition and civil construction, were other aspects commonly identified in the basins, which indicated absence or low frequency of maintenance practices. It was also verified the filling of more than half of the units and its emptying in less than 24 hours, not being observed or reported overflow of the units. Regarding the dimensioning, it was observed the adoption of two methodologies to calculate the volume of detention and the discrepancy between these values. The estimated costs of implementation varied from R$32.16/m² to R$75.13/m² and from R$21.4/m³ to R$25.8/m³. The maintenance cost was R$333.00 per practice. The surrounding population was in favor of the units, as long as they have frequent maintenance and multifunctionality of these spaces, public policies are necessary to encourage its integration with their surroundings, favoring its appropriation by their community.